Perubahan Wewenang Penghulu Pasca Keluarnya Staatsblad 1937 No 116 Kasunanan Surakarta Tahun 1937-1940 M - triyanta, agus (El Tarikh : Journal of History, Culture and Islamic Civilization, 2020)
The leader is a religious officer who is part of the traditional bureaucracy in Kasunanan Surakarta. In charge of taking care of religious matters, judges at the religious court maintain the continuity of Islamic law in Kasunanan Surakarta. Along with the strong influence of the Dutch colonial government in Kasunanan Surakarta in the 19th century AD, it brought major changes to the authority of the head of the Kasunanan Surakarta. The Dutch colonial government policy issued a regulation published in Staatsblad (State Sheet) of 1937 No. 116 regulating the authority of the pengulu limited to family law. The policy of the Dutch colonial government caused a strong reaction of protests among the top leaders of all Javanese Madura gathered in Surakarta against the policy of the Dutch colonial government to express rejection of the issuance of a regulation published in Staatsblad 1937 No 116. Dutch colonial government policy issued Staatsbalad regulations 1937 number 116 in Kasunan Surakarta it is a form of castration of Islamic law replaced by customary law with the aim of facilitating the movement of the colonial government to control the land owned by the land of Putara. This research uses historical methods and uses a sociological approach and uses the concepts used in this study, the concept of the upstream, change, and authority. This research uses historical methods consisting of heuritic, verification, interpretation and historiography to collect data using the library study (Liberay Rereach). This paper focuses on changes in the authority of the leader after the release of Staatsblad 1937 No 116 in Kasunan Surakarta.Keywords: Changes in the Wewenang, Penghulu,  Kasunanan Surakarta